Validation of the English-language version of 5-item Oral Health Impact Profile. Issue 2 (April 2016) - Naik, Amruta; John, Mike T.; Kohli, Nidhi; Self, Karl; Flynn, Priscilla
Abstract: Purpose: The Oral Health Impact Profile (OHIP) is currently the most widely used oral health-related quality of life (OHRQoL) instrument. The study validated the English-language 5-item OHIP by investigating its psychometric properties of dimensionality, reliability, and validity in the adult general population. Methods: In 405 subjects (mean age 45 + 15.7 years, 63% female) from the 2014 Minnesota State Fair, dimensionality was investigated by confirmatory factor analysis. Construct validity was assessed by using a structural equation model correlating OHRQoL and self-reported global oral health status. Reliability was calculated using Cronbach's alpha for OHIP5 total scores. Results: In the confirmatory factor analysis, the unidimensional model fit OHIP5 well as indicated by fit indices (RMSEA: 0.07, SRMR: 0.03, comparative fit indices: >0.95). In the structural equation model, self-reported global oral health status correlated with 0.46 with the latent OHRQoL factor, indicating sufficient construct validity. Cronbach's alpha, a measure of score reliability, was "satisfactory" with 0.75. Conclusion: We validated the English-language version of OHIP5 in the adult general population. Ultrashort instruments such as the 5-item OHIP provide a conceptually appealing and technically feasible opportunity to measure the impact of oral disorders and dental interventions in settings such as general dental practice where the burden to collect and interpret OHRQoL information needs to be minimized.